Arbitration and Disputes in Road Works – Peruvian MARC - Huamán Guerrero, Néstor Wilfredo (2025)
This article was presented by the author in the XIV Ibero-Latin American Asphalt Congress (XIV CILA), that took place in La Habana, Cuba, between November 18th and 25th, 2007; and it provides an opportunity for other Spanish speaker countries to learn from the Peruvian experience in conflict solutions, capable of solving the permanent controversies that usually take place during road construction, as well as in other engineering areas. These controversies definitely impact on the final cost of the works, due to their technical-legal dependence. The results are decisive for both parties in the conflict, those in favor and those against, since its application usually implies significant payments in favor of the winning party. This norm is under the scope of the Law of State Contracts and Acquisitions, valid in Peru since 1998.